A Double-Blinded Placebo Randomized Controlled Trial Evaluating Short-term Efficacy of Platelet-Rich Plasma in Reducing Postoperative Pain After Arthroscopic Rotator Cuff Repair: A Pilot Study. (January 2015) - Hak, Alisha; Rajaratnam, Krishan; Ayeni, Olufemi R.; Moro, Jaydeep; Peterson, Devin; Sprague, Sheila; Bhandari, Mohit
Background: We aimed to determine whether patients with arthroscopically repaired rotator cuff (RC) tears would have reduced pain and improved function after ultrasound-guided platelet-rich plasma (PRP) injections compared with placebo injection. Hypothesis: PRP compared with placebo (saline) was more effective in reducing pain at the site of an RC injury that has undergone arthroscopic repair. Study Design: Randomized controlled trial. Level of Evidence: Level 2. Methods: We conducted a 2-centered, blinded, randomized controlled trial comparing the level of pain in patients undergoing arthroscopic repair. Patients were randomized to either PRP or saline (placebo). They received 2 ultrasound-guided injections of the randomized product: 1 intraoperatively and 1 at 4 weeks postoperatively. The primary outcome measure was shoulder pain demonstrated using a visual analog scale (VAS) at 6 weeks postoperatively. Secondary outcomes included the EuroQol-5 Dimensions (EQ-5D); the Western Ontario Rotator Cuff Index (WORC); and the Disabilities of the Arm, Shoulder, and Hand Score (DASH), as well as adverse events and revision surgeries. Patients were assessed clinically preoperatively and at 2, 4, and 6 weeks postsurgery. A prespecified interim analysis was conducted after 50% of patients were recruited and followed. Results: We recruited 25 patients when interim power analysis led to an early trial termination. Follow-up was 96%. The mean difference between groups was not statistically significant (–1.81; 95% CI, –4.3 to 1.2; P = 0.16). The EQ-5D, WORC, and DASH scores also did not show significant differences between groups at week 6 ( P = 0.5, 0.99, and 0.9, respectively). There were no revision surgeries, and 4 adverse events (3 PRP, 1 saline). Conclusion: There was no statistical difference in outcome measures when augmenting arthroscopically repaired RC tears with PRP. Clinical Relevance: Identifying therapies that improve outcomes in patients with RC tears remains a challenge and deserves ongoing investigation.